1975
DOI: 10.1161/01.cir.52.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in medically-treated coronary artery disease: influence of ejection fraction compared to other parameters.

Abstract: The prognostic value of the left ventricular ejection fraction(EF) was compared to that of other commonly used indices--severity of coronary artery disease, left ventricular end-diastolic pressure, cardiac index, and abnormal ECG--in 144 patients with coronary artery disease followed for an average of 14 months on medical management. During this period, 14 patients (10%) died. Analysis of the mortality demonstrated that the EF was the most powerful predictor of short-term survival. Thus, patients with three-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…However, the left ventricular ejection fraction is a powerful predictor of shortand long-term survival.8' 14, 16 Nelson et al 8 found that ejection fraction was a more discriminant prognosticator than the severity of angiocardiographic coronary disease or the clinical functional class. Schulze et al 22 found that survivors of acute myocardial infarction with a predischarge radionuclide ejection fraction > 0.40 had an overall good prognosis.…”
Section: Ejection Fractionsmentioning
confidence: 99%
“…However, the left ventricular ejection fraction is a powerful predictor of shortand long-term survival.8' 14, 16 Nelson et al 8 found that ejection fraction was a more discriminant prognosticator than the severity of angiocardiographic coronary disease or the clinical functional class. Schulze et al 22 found that survivors of acute myocardial infarction with a predischarge radionuclide ejection fraction > 0.40 had an overall good prognosis.…”
Section: Ejection Fractionsmentioning
confidence: 99%
“…The measurement of ejection fraction is a more direct and clinically useful assessment of ventricular function (Cohn and Gorlin, 1975;Nelson et al, 1974) and with the technique used in this study is less invasive than the standard angiographic technique, requiring only a venous catheter. Similar findings have been reported recently by DeMaria et al (1978).…”
Section: Discussionmentioning
confidence: 99%
“…Since it is generally accepted that the state of ventricular function is a powerful prognostic sign in patients with coronary artery disease (Cohn and Gorlin, 1975;Nelson et al, 1974) any intervention which might alter ventricular function is of potential significance.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques and protocols involved in both methods have been previously described in detail." 2 Briefly, the epinephrine ventriculogram was performed in 14 subjects approximately 30 min after the control ventriculogram, and 9 min after a [1][2][3][4] ,ug/min infusion of l-epinephrine had begun. Ejection March 1975 for introducing ventricular premature contractions when this device is not available: 1) by pulling a catheter back through the right ventricle into the right atrium, and 2) as a result of the power injection of angiographic contrast medium into the left ventricle.…”
Section: Contractile Reserve and Prognosis In Cad Catheterization Stumentioning
confidence: 99%